How do fiscal and technology shocks affect real exchange rates? New evidence for the United States - Zeno Enders; Gernot J. Müller; Almuth Scholl (Goethe University Frankfurt, Center for Financial Studies (CFS), 2008)
Using vector autoregressions on U.S. time series relative to an aggregate of industrialized countries, this paper provides new evidence on the dynamic effects of government spending and technology shocks on the real exchange rate and the terms of trade. To achieve identification, we derive robust restrictions on the sign of several impulse responses from a two-country general equilibrium model. We find that both the real exchange rate and the terms of trade whose responses are left unrestricted depreciate in response to expansionary government spending shocks and appreciate in response to positive technology shocks.
urn:nbn:de:hebis:30-56955
Keywords: F41; F42; E32; 330; Real Exchange Rate; Terms of Trade; International Transmission Mechanism; Government Spending Shocks; Technology Shocks; VAR; Sign Restrictions; Kaufkraftparität; Terms of Trade; Öffentliche Ausgaben; Technologie; Schock; Internationaler Preiszusammenhang; Zwei-Länder-Modell; Allgemeines Gleichgewicht; Schätzung; USA